The Effect of the Two Stay Two Stray (TSTS) Cooperative Learning Model on Fourth-Grade Students’ Mathematical Conceptual Understanding - Weni Putri Isriani; Ulandari Safitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The ability to understand mathematical concepts is one of the essential competencies that should be developed through mathematics learning. However, mathematics instruction in Grade IV at SDN 06 Punggung Ladiang and SDN 12 Cubadak Mentawai has not optimally engaged students in constructing concepts independently, resulting in low levels of conceptual understanding. To address this issue, the Cooperative Learning model of the Two Stay Two Stray (TSTS) type was implemented as an alternative instructional strategy. This study aimed to determine whether students taught using the TSTS model achieved better mathematical conceptual understanding than those taught through conventional learning. The study employed a quasi-experimental method with a Static Group Design. Grade IV students of SDN 06 Punggung Ladiang were assigned as the experimental group and received instruction using the TSTS model, whereas Grade IV students of SDN 12 Cubadak Mentawai served as the control group and were taught conventionally. The results of data analysis indicated that students who learned through the Cooperative Learning model of the Two Stay Two Stray type demonstrated better mathematical conceptual understanding than those who received conventional instructio.